Sustainable Turkey Farming: The Role of Hydroponic Sprouted Fodder in Feed Optimization - Yasmin, Kanis; Rashedi, Mobasser Ahmed; Mehta, Basant Kumar; Salma, Ummay; Miah, Abdul Gaffar (International Journal of Applied Sciences and Biotechnology, 2025)
Hydroponic fodder has gained attention as an innovative and sustainable feed resource for poultry production. This study assessed the effects of hydroponic maize and sesbania sprouted fodder as partial replacements for commercial concentrate feed (CCF) in turkey production, with a focus on growth parameters, feed intake, feed conversion efficiency (FCE), and economic viability. Forty-eight turkeys (eight-week-old) were randomly divided into four dietary treatment groups: T1 (100% CCF), T2 (90% CCF + 10% hydroponic fodder), T3 (70% CCF + 30% hydroponic fodder), and T4 (60% CCF + 40% hydroponic fodder). Results revealed that hydroponic maize contained 14.79% dry matter (DM) and 10.92% crude protein (CP), while sesbania had 9.46% DM and 37.26% CP, demonstrating its potential as a high-protein alternative. Among the treatment groups, the highest (P<0.05) daily weight gain (20.61 g/day) was observed in birds of T2 group, which also recorded the best (P<0.05) FCE (4.03) and the highest (P<0.05) profitability index (0.36). Economic analysis showed that T2 had the highest (P<0.05) net farm income, making hydroponic fodder supplementation a cost-effective strategy. Additionally, hydroponic fodder improved gut health, enhanced nutrient bioavailability, and reduced oxidative stress, as evidenced by 100% survivability across all groups. These findings align with previous research supporting the role of hydroponic sprouts in poultry nutrition. The results suggest that incorporating hydroponic fodder at optimal levels can improve turkey growth and economic efficiency while promoting sustainable poultry farming. Future research should explore the long-term effects of hydroponic fodder on carcass quality, immune response, and environmental sustainability. Int. J. Appl. Sci. Biotechnol. Vol 13(3): 139-145.